2017
DOI: 10.1080/07315724.2017.1370618
|View full text |Cite
|
Sign up to set email alerts
|

Protein Supplement Usage Among Male University Students: Comparisons Between Current and Previous Users

Abstract: The market for protein supplements has been growing, so measuring consumers' attitudes and satisfaction would help attract potential consumers. In addition, analyzing previous users' opinions on products could guide product development and encourage customers to return for repurchase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…The main results regarding protein consumption have highlighted a uniformity amongst supplementation with a percentage intake in line with that expressed in other studies in different geographical locations [1, 4, 7, 9, 10, 11]. Whilst the statistical difference was not significant across groups, it is worth mentioning that the UK population reported a consumption of 51.9%.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The main results regarding protein consumption have highlighted a uniformity amongst supplementation with a percentage intake in line with that expressed in other studies in different geographical locations [1, 4, 7, 9, 10, 11]. Whilst the statistical difference was not significant across groups, it is worth mentioning that the UK population reported a consumption of 51.9%.…”
Section: Discussionsupporting
confidence: 84%
“…The mainly used supplements were vitamins/minerals followed by protein powders and weight loss products. A higher prevalence is generally found in gym users, with values ranging from 29.4% to 47.5% [1, 4, 7, 9, 10, 11]. Gym users (who are mainly resistance training practitioners) prevalently declare the use of protein supplements, followed by vitamins/minerals, branched chain amino acids and creatine a means to enhance performance or support intense training regimes [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence remained consistent throughout all colleges. Evidence indicates that protein supplementation is quite common among male university students as it improves physical performance [ 28 , 29 ]. Multivitamin use prevailed in all colleges with highest prevalence in business college, i.e., around 23% and lowest in nursing college, i.e., 9.1%.…”
Section: Discussionmentioning
confidence: 99%
“…This may be based on individual buying preference. Studies have demonstrated that an individual may prefer brands as brand products are believed to have better quality as compared to generics [ 15 , 28 ]. Dwyer and colleagues have reported that poor quality of dietary supplements have resulted in adverse drug events (ADEs) and mortality [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The instrument contains DSs usage information, general health conditions, perceptions towards health behaviors, nutritional knowledge, and demographics. Questions asking DSs usage were excerpted from [32]. The questionnaire also consists of four health-related statements to be rated on a five-point Likert scale (1: not very good , 5: very good ), which were also adapted from previous research [32,33].…”
Section: Methodsmentioning
confidence: 99%